Multilevel Regression Analysis on Graduate Student Grade Point Average - Riswan, Riswan; Dyah Syafitri, Utami; Nur Aidi, Muhammad (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2024)
Abstract:Multilevel regression is one of the methods used to analyze hierarchical data structures. One case of data with a hierarchical structure is the cumulative grade point average (GPA) data for students each semester (level one) which is nested within students (level two), and nested within faculties (level three). This study produced the three best three-level regression models: the multilevel regression model, the multilevel regression model with natural logarithmic transformation, and the multilevel binary logistic regression model. The multilevel regression model and the multilevel regression model with natural logarithmic transformation at a significant level of 5%, have the same variables that affect student GPA scores, including semesters, credits, gender, scholarships, and marital status with the same interaction effect, namely semester interactions with scholarships. In addition, the ICC values by the two models are also the same which explains that 91% of the total diversity of student GPA comes from the student level and 8% comes from the faculty level. For the multilevel binary logistic regression model, all explanatory variables affect GPA without involving interaction between levels. Abstrak:Regresi multilevel merupakan salah satu metode yang digunakan untuk menganalisis struktur data hirarkhi. Salah satu kasus data dengan struktur hirarki adalah data indeks prestasi kumulatif (IPK) mahasiswa tiap semester (level satu) yang tersarang dalam mahasiswa (level dua), tersarang dalam fakultas (level tiga). Dalam penelitian ini menghasilkan tiga model regresi tiga level terbaik yaitu model regresi multilevel, model regresi multilevel dengan transformasi logaritma natural, dan model regresi logistik biner multlevel. Model regresi multilevel dan model regresi multilevel dengan transformasi logaritma natural pada taraf nyata 5%, memiliki peubah sama yang berpengaruh terhadap nilai IPK mahasiswa antara lain semester, SKS, jenis kelamin, beasiswa, dan status nikah dengan pengaruh interaksi yang sama yaitu interaksi semester dengan beasiswa. Selain itu, nilai ICC oleh kedua model tersebut juga sama yang menjelaskan bahwa 91% total keragaman IPK mahasiswa berasal dari level mahasiswa dan 8% berasal dari level fakultas. Untuk model regresi logistik biner multilevel semua peubah penjelas berpengaruh terhadap IPK tetapi tanpa melibatkan interaksi antar level.